Perspektif Dalang Mbah Demang dalam Upaya Meraih Kesejahteraan Masyarakat dan Pembangunan yang Berkelanjutan : The Perspective of Mbah Demang the Puppeteer in Pursuing Community Welfare and Sustainable Development - Purwandhanto, Vanisa Nakita; Budiman, Hanif; Pramansari, Putu Ayu (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2025)
This study explores the Mbah Demang Tradition's role in achieving community welfare and sustainable development in Banyuraden Village. Using qualitative methods and a case study approach, this study focuses on the sustainability values ​​contained in the tradition and their impact on the local community's social, cultural, and economic life. Data were collected through in-depth interviews, observations, and documentation, which were then analyzed thematically. The study results indicate that the Mbah Demang Tradition significantly strengthens social solidarity, maintains the balance of nature, and preserves local cultural values ​​that support long-term welfare.